Simulation analysis of fin stabilizer on ship roll control during turning motion. (15th September 2018) - Lihua, Liang; Peng, Zhao; Songtao, Zhang; Ming, Ji; Jia, Yuan
Abstract: Ship turning motion is an important part of ship maneuverability and is directly related to the safety of the ship sailing at sea. Ships experience a certain amount of rolling and heeling during turning. The rolling and heeling caused by turning and waves can be large enough to affect the ability of ships to perform their missions. Fin stabilizers are currently added to ship designs for the primary purpose of producing roll-canceling moments during ordinary operation. The present work aims to investigate the effect of fin stabilizers on ship roll reduction control during turning motion. The 6-DOF mathematical model of a multipurpose navy vessel as well as the models of forces and moments caused by hydrodynamic, propeller, rudder, fins and waves are established in MATLAB. Based on the simulation analysis of ship turning motion with and without fin stabilizers, a MIGA-based improved PID controller is developed. The simulation results of ship roll control during turns using the MIGA-PID controller are compared with the results of ZN-PID and LQR controllers. Simulation results show that fin stabilizers are also effective for roll reduction control during ship turns with an appropriate controller, and the present developed MIGA-PID controller can be a practical choice. Highlights: The 6-DOF mathematical model of a multipurpose naval vessel is established. The models of hydrodynamic, propeller, rudder, fin and disturbance are established. Ship turning motions with and without fin stabilizers are simulated and analyzed. A MIGA-based improved PID controller is developed to control fin stabilizers. The effect of fin stabilizers on ship roll reduction control during turns is analyzed.